2015
DOI: 10.1016/j.palaeo.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous (Maastrichtian) shallow water hydrocarbon seeps from Snow Hill and Seymour Islands, James Ross Basin, Antarctica

Abstract: 22Fossil hydrocarbon seeps are present in latest Cretaceous (Maastrichtian) volcaniclastic shallow shelf 23 sediments exposed on Snow Hill and Seymour Islands, James Ross Basin, Antarctica. The seeps occur 24 in the Snow Hill Island Formation on Snow Hill Island and are manifest as large-sized, cement-rich 25 carbonate bodies, containing abundant thyasirid bivalves and rarer ammonites and solemyid bivalves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 106 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…The ammonites have δ 13 C values lower than the other taxa, with the baculites intermediate between the scaphites and sphenodiscids, suggesting differences in diet and/or position within the water column. Tobin and Ward (39) also documented lower average δ 13 C values in Late Cretaceous ammonites relative to benthic mollusks; however, these differences may be due to methane-derived carbon incorporated into the shells (40). The warm temperature recorded by the sphenodiscids, combined with low δ 13 C, supports the notion that these organisms generally lived close to shore; if they lived in the surface waters of the study site, they would have been exposed to a higher δ 13 C DIC , as indicated by the planktonic foraminifera δ 13 C. Thus, the marked δ 13 C differences between sphenodiscids and planktonic foraminifera reinforce the conclusion of offshore postmortem transport of sphenodiscids based on taphonomic observations.…”
Section: Resultsmentioning
confidence: 99%
“…The ammonites have δ 13 C values lower than the other taxa, with the baculites intermediate between the scaphites and sphenodiscids, suggesting differences in diet and/or position within the water column. Tobin and Ward (39) also documented lower average δ 13 C values in Late Cretaceous ammonites relative to benthic mollusks; however, these differences may be due to methane-derived carbon incorporated into the shells (40). The warm temperature recorded by the sphenodiscids, combined with low δ 13 C, supports the notion that these organisms generally lived close to shore; if they lived in the surface waters of the study site, they would have been exposed to a higher δ 13 C DIC , as indicated by the planktonic foraminifera δ 13 C. Thus, the marked δ 13 C differences between sphenodiscids and planktonic foraminifera reinforce the conclusion of offshore postmortem transport of sphenodiscids based on taphonomic observations.…”
Section: Resultsmentioning
confidence: 99%
“…Besides an abundant and diverse molluscan fauna, other common faunal elements found throughout the Maastrichtian portion of the López de Bertodano Formation include serpulid worm tubes ( Rotularia ), cidaroid echinoid spines, scaphopods, rare solitary corals, decapod crustaceans, marine reptiles, shark vertebrae and fossil wood bored by Teredolites 26 27 33 . Recent work has also revealed the presence of fossil methane seeps, which are periodically developed on the Maastrichtian sea-floor and are characterized by a distinctive benthic molluscan fauna 34 .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the Amma Fatma seep fauna contains mostly elements of normal marine background faunas, and lacks specialized obligate taxa, possibly apart from the lucinid, which might belong to the seep obligate genus Nymphalucina (Kiel, ), although is also similar to the lucind figured in El Qot (, plate 14, figs 7 to 10) as Lucina fallax Forbes, 1846 from the Late Cenomanian of Egypt. This paucity of obligate seep taxa is a common feature of shallow water seep faunas in the Mesozoic and Cenozoic (Kiel, ; Little et al ., ). Other examples include the slightly older Cenomanian Tropic Shale seep faunas from southern Utah, USA (Kiel et al ., ), which are dominated by mostly small specimens of the bivalve genera Inoceramus and Nymphalucina , the gastropod genus Drepanochilus , rarer examples of the neogastropod Paleopsephaea and Callianassa decapod claws.…”
Section: Interpretation and Discussionmentioning
confidence: 97%
“…Despite the occurrence of macrofossils in zone 4, the Amma Fatma body is poor in fossils compared to most Phanerozoic seep deposits, which are usually replete in shelly macrofauna (Campbell & Bottjer, ; Kiel & Peckmann, ; Little et al ., ). Most of the shells identified in thin sections are severely fragmented and were most likely transported to the site over some distance, indicating that most of these molluscs did not live at the seep.…”
Section: Interpretation and Discussionmentioning
confidence: 97%